Analysis of halogen-specific TOX revisited: Method improvement and application - Kristiana, Ina; McDonald, S.; Tan, J.; Joll, C.; Heitz, A. (Elsevier, 2015)
A method was optimised and evaluated for the analysis of total organic halogen (TOX) in drinking water samples. It involved adsorption of organic halogen onto activated carbon, followed by combustion of the activated carbon and adsorbed material, absorption of the resulting hydrogen halide gases in an absorbing solution, and analysis of halide ions in the solution using an on-line ion chromatograph. Careful optimisation and validation of the method resulted in significant improvements compared to previously reported methods. Method detection limits were 5 µg L−1 for TOCl (as Cl−), 2 µg L−1 for TOBr (as Br−), and 2 µg L−1 for TOI (as I−). Interferences with TOI measurement occurred when iodide or iodate was present in the sample at concentrations at or above 100 µg L−1 and 500 µg L−1, respectively. In general, excellent method recoveries were determined for a wide range of model compounds. The method was used to investigate the formation of halogen-specific TOX through a water treatment plant and in laboratory-scale disinfection experiments. Up to 70% of bromide in the water was converted to TOBr following disinfection at the plant. In the disinfection experiments, TOI was preferentially formed in chloraminated samples, and trihalomethanes only constituted a small fraction (≤20%) of TOX, highlighting the significant proportion of halogenated organic DBPs that are not measured regularly. This is the first report of a comprehensive assessment of the key parameters influencing the efficiency and reliability of the analysis of halogen-specific TOX in drinking water with demonstration of its applications.